Parceiras de maré : uma etnografia sobre as pescadoras do Bom Jesus, Sergipe - Castro, Érika Sousa Vieira de (2019)
The present dissertation is about a group of fisherwomen from Bom Jesus dos Navegantes, a neighborhood located in the municipality of Laranjeiras, Sergipe, whose artisanal fishing is not done at sea, but in the mangrove and in the Sergipe River. In this location, the fisherwomen stand out for being mostly pivots of re-productive work and, consequently, the main generators of family income. The objective of this research is to understand what it is like to be and become a fisherwoman in Bom Jesus, understanding that artisanal fishing is still naturalized as a male profession and, in the case of Bom Jesus, this is transfigured. Diving a little deeper into this specific cosmology, I realized that the tide transcends the notion of work, as it is also represented as a space of feminine appropriation, as well as the social universe built in the community itself, in which issues related to life, learning, leisure, autonomy and partnerships. Being a work performed by women, fishing is a tide of uncertainty, because, on the one hand offers certain guarantees of survival, but on the other, it generates damages of various types and levels triggered by the inviabilization of this craft by the institutions, community and government. Affected from personal experience, by accompanying these fisherwomen in the mangroves and in the river, the wrappings that represent their realities were also analyzed through a look at bodies and emotions.